POST-BASIC TRAINING EVALUATION FOR CIVIL SERVANT CANDIDATES: ANALYSIS OF ANEKA VALUE IMPLEMENTATION IN IMPROVING PUBLIC SERVICE QUALITY AT THE MINISTRY OF RELIGIOUS AFFAIRS OF NORTH SUMATRA PROVINCE - Mahmun Syarif (Program Pascasarjana UIN Sumatera Utara, 2026)
Basic Training (Latsar) for Civil Servant Candidates (CPNS) constitutes a strategic policy instrument designed to internalize the core values of the state civil apparatus in order to promote the continuous improvement of public service quality. This study aims to evaluate the sustainability of the implementation of the ANEKA core values—Accountability, Nationalism, Public Ethics, Quality Commitment, and Anti-Corruption—among alumni of the 2019 Batch of Group III CPNS Basic Training within the Regional Office of the Ministry of Religious Affairs of North Sumatra Province. Employing a qualitative approach grounded in Kirkpatrick’s training evaluation model at Level 3 (Job Behaviour) and Level 4 (Results), this study critically examines the strategic roles of coaches and mentors, as well as the use of information technology, in facilitating the transfer of training. The study involved 310 informants selected through purposive sampling, comprising Latsar alumni, colleagues, mentors or immediate supervisors, heads of work units, and coaches from the Medan Religious Education and Training Centre. Data were collected through in-depth structured interviews, participatory observation in public service units, and document analysis of actualization reports. Data were analysed using the interactive model developed by Miles and Huberman. The findings indicate that, although participants’ actualization performance during the training was assessed as highly satisfactory, the consistency and sustainability of its implementation declined significantly after the participants were formally appointed as full civil servants. This decline was attributed to weak post-training monitoring systems, limited continuous guidance from mentors, and the strong influence of conventional workplace cultures, particularly seniority. The optimization of information technology and the strengthening of organizational commitment were identified as key determinants in maintaining the sustainability of public service quality.